2018
DOI: 10.1159/000481618
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Kidney Disease Elicits an Intestinal Inflammation Resulting in Intestinal Dysmotility Associated with the Activation of Inducible Nitric Oxide Synthesis in Rat

Abstract: This study was conducted to investigate whether chronic kidney disease (CKD) affects intestinal inflammation and intestinal motility and the underlying mechanisms. Rats were randomized into control group and uremic group. Uremia rats were induced by the 5/6 kidney resection, while the control went through the same procedures but without any kidney resection. Intestinal motility was assessed by charcoal transport assay; intestinal inflammation was assessed by analyses of levels of tumor necrosis factor (TNF)-α,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Another pathogenic factor that potentially links CKDrelated gut dysbiosis to constipation may be intestinal inflammation. Yu et al showed that intestinal motility in CKD rats underwent 5/6 nephrectomy was significantly HD hemodialysis, PD peritoneal dialysis decreased compared with that in the control rats [17]. The expression levels of interleukin-6, tumor necrosis factor-α, and inducible nitric oxide synthesis were increased in the gut of uremic rats.…”
Section: Gut Dysbiosismentioning
confidence: 99%
See 1 more Smart Citation
“…Another pathogenic factor that potentially links CKDrelated gut dysbiosis to constipation may be intestinal inflammation. Yu et al showed that intestinal motility in CKD rats underwent 5/6 nephrectomy was significantly HD hemodialysis, PD peritoneal dialysis decreased compared with that in the control rats [17]. The expression levels of interleukin-6, tumor necrosis factor-α, and inducible nitric oxide synthesis were increased in the gut of uremic rats.…”
Section: Gut Dysbiosismentioning
confidence: 99%
“…Wu et al reported that the colonic transit time of patients treated with hemodialysis (HD) or peritoneal dialysis (PD) was significantly longer than that of age and sex-matched healthy subjects [15]. Delayed intestinal transit was also observed in CKD animal models [16][17][18]. Thus, constipation in CKD may primarily be classified as the slow transit type.…”
Section: Prevalence Of Constipation In Ckdmentioning
confidence: 99%
“…The colonic transit time increased from 24 ± 12 h in healthy subjects to 33 ± 14 h in continuous ambulatory peritoneal dialysis patients and 43 ± 22 h in hemodialysis patients [46]. Elongated intestinal transit was observed in the SNx rat model [17][18][19] and the mouse model induced by an adenine-enriched diet [20]. In contrast, oro-anal transit and colonic transit times were decreased in SNx dogs [16].…”
Section: Motility Dysfunction and Gut Barriermentioning
confidence: 99%
“…As optimal intestinal motility is critical to nutrition and several biological functions, the loss of normal gut function compromises nutrition and results in prolonged hospital stay 2,5 . GIT dysmotility can be the result of several disease processes, including but not limited to inflammatory bowel disease, 6,7 chronic kidney disease, 8,9 peritonitis, 10,11 hemodynamic instabilities, 12–14 neurodegenerative disorders, 15–17 and spinal cord injury 18 . The pathophysiological mechanisms of GIT dysmotility are multifactorial.…”
Section: Introductionmentioning
confidence: 99%